1998
DOI: 10.1038/32183
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells acquire antigen from apoptotic cells and induce class I-restricted CTLs

Abstract: CD8+ cytotoxic T lymphocytes (CTLs) mediate resistance to infectious agents and tumours. Classically, CTLs recognize antigens that are localized in the cytoplasm of target cells, processed and presented as peptide complexes with class I molecules of the major histocompatibility complex (MHC). However, there is evidence for an exogenous pathway whereby antigens that are not expected to gain access to the cytoplasm are presented on MHC class I molecules. The most dramatic example is the in vivo phenomenon of cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
1,415
9
10

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,091 publications
(1,491 citation statements)
references
References 29 publications
47
1,415
9
10
Order By: Relevance
“…Studies have shown that DC can take up antigen from dying cells and cross-present the antigenic material onto both MHC I and MHC II [20,21]. However, these studies relied on the use of mature DC to phagocytose apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that DC can take up antigen from dying cells and cross-present the antigenic material onto both MHC I and MHC II [20,21]. However, these studies relied on the use of mature DC to phagocytose apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, our findings show that necrotic DC, irrespective of their maturation status are not immunostimulatory, which may be due to the paucity of the presence of certain immunosuppressive factors in primary DC, rendering them nonimmunogenic even after the cellular contents are released into the extracellular milieu. However, such factors still need to be identified.Studies have shown that DC can take up antigen from dying cells and cross-present the antigenic material onto both MHC I and MHC II [20,21]. However, these studies relied on the use of mature DC to phagocytose apoptotic cells.…”
mentioning
confidence: 99%
“…It is well established that DCs require CD4 þ T-cell help to cross-prime CD8 þ T cells properly and this process depends on the stimulation of CD40 receptor on DCs by transiently expressed CD40L on CD4 þ T cells. 40 CD40L also provides the primary stimulus for induction of IL-12, which is critically important for generation of CTL,41 by mature DCs. [42][43][44] In vitro, CCL21 has been reported to be a chemotactic factor for CD4 þ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been reported that dendritic cells e ciently present antigen from apoptotic cells, stimulating class I-restricted CD8 + cytotoxic T lymphocytes (Albert et al, 1998). Phagocytic engulfment of apoptotic cells in the tumour mass should lead to enhanced antigen presentation and possibly heightened anti-tumour immune responses.…”
Section: Discussionmentioning
confidence: 99%